2013
DOI: 10.1371/journal.pone.0068048
|View full text |Cite
|
Sign up to set email alerts
|

Permanent and Transient Congenital Hypothyroidism in Fayoum, Egypt: A Descriptive Retrospective Study

Abstract: BackgroundCongenital hypothyroidism (CH) is one of the most common preventable causes of mental retardation. One important challenge in understanding the epidemiology of CH is that some newborns will have transient CH, a temporary depression of thyroid hormone concentrations that can last from several days to several months. Studies from other countries have reported that 10 to 15% of children treated for CH ultimately prove not to need treatment past 3 years of age to maintain normal hormone concentrations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
4
29
4
1
Order By: Relevance
“…Our findings on the high frequency of transient hypothyroidism are also consistent with those of Hashemipour et al, Dorrea and Ordookhani et al (16, 23, 24). Nevertheless, our findings are not in agreement with the results from other countries which have reported that 10 to 15% of children treated for CH ultimately have transient hypothyroidism (8, 20, 22). In alignment with previous studies carried out in Iran (17, 25-28), we assume that the high frequency of transient CH in Iran may be due to iodine deficiency or overload, although Iran is no longer recognized as an iodine deficient area.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings on the high frequency of transient hypothyroidism are also consistent with those of Hashemipour et al, Dorrea and Ordookhani et al (16, 23, 24). Nevertheless, our findings are not in agreement with the results from other countries which have reported that 10 to 15% of children treated for CH ultimately have transient hypothyroidism (8, 20, 22). In alignment with previous studies carried out in Iran (17, 25-28), we assume that the high frequency of transient CH in Iran may be due to iodine deficiency or overload, although Iran is no longer recognized as an iodine deficient area.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the most common etiology of CH was dyshormonogenesis as indicated in the studies conducted by Hashemipour et al (9) and Karamizadeh et al (19) in Iran, a relatively high rate of parental consanguinity (25%) among infant with congenital hypothyroidism could account for the increased incidence of CH in our region. In support of the previous data, we also propose that the inclusion of infants of transient hypothyroidism increased the reported incidence rate of CH (8, 20). However, the effects of genetic background, autoimmune and environmental factors cannot be omitted.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In Korea, a total of 13 laboratories perform the NBS TSH, and the cutoff levels of TSH vary from 10.0 to 22.5 mIU/mL according to each laboratory protocol (8). Another recent study from Korea showed that nearly 80% of preterm infants with CH treated for 3 years with thyroxine were later diagnosed with transient hypothyroidism (9 (11). Infants with trisomy 21 (Down syndrome) have a higher incidence of hypothyroidism detected by NBS programs, occurring as commonly as 1:50 newborns but they rarely have transient hypothyroidism (12).…”
Section: Epidemiologymentioning
confidence: 99%
“…Data from another large screening program in Lebanon report a prevalence of 1: 1,700 [27]. These rates are comparable to those reported from the United Arab Emirates (1: 1,873) [28], and from the Greek Cypriot population (1: 1,800) [29] but higher than some of the reported rates from Turkey (1: 2,326) [22], Egypt (1: 3,587) [23], and from different regions in Saudi Arabia (1: 2,759 [24] and 1: 4,208 [25]). Nevertheless, this apparently higher rate in the overall incidence of congenital hypothyroidism in Lebanon does not explain the magnitude of the increase in the rates detected in our population of VLBW infants.…”
Section: Discussionmentioning
confidence: 58%